Learning Based Spectrum Sensing in OFDM Cognitive Radios - Muzaffar, Muhammad Umair (2012)
A Master of Science thesis in Electrical Engineering by Muhammad Umair Muzaffar entitled, "Learning Based Spectrum Sensing in OFDM Cognitive Radios," submitted in May 2012. Thesis advisor is Dr. Mohamed El-Tarhuni and thesis co-advisor is Dr. Khaled Assaleh. Available are both soft and hard copies of the thesis.